They never said it would be easy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Is agriculture a way of life, or a way of living? Treated by outsiders as a quaint backwater, abandoned by insiders as a lost cause, it is running itself into the ground. Time for some plain talking about who runs where, and what, next.Among the...